Phase transition anomaly observed in PbZrO3/Al2O3nanocomposites - C. Puchmark (2018)
Effects of Al2O3nanoparticle additions on the phase transitions of PbZrO3/Al2O3nanocomposites were investigated. The nanocomposites were prepared by a solid-state reaction method. The phase transition behaviour of the composites was studied by dielectric measurements and differential scanning calorimetry. Nanoparticle additions produced a significant reduction in the temperature of the phase transition from ferroelectric to antiferroelectric phase during the cooling measurement. This resulted in a large thermal hysteresis. The results indicated that the intermediate ferroelectric phase of PbZrO3is very sensitive to the Al2O3impurity. It is proposed that changes in defect chemistry due to the reaction between the nanoparticles and the matrix during sintering are responsible for the anomaly in phase transition behaviour. © 2010 Taylor & Francis.